Benefits and functionality of an interorganisational workplace health management network – insights from the companies’ perspective - Hente, Luisa; Schlesinger, Torsten (Frontiers in Public Health, 2024)
Introduction Workplace health management (WHM) is a worthwhile investment for companies. Nevertheless, the implementation of health-promoting interventions remains limited, especially in small and medium-sized enterprises. Interorganisational networks could be a promising way to raise awareness of the advantages of implementing WHM. Therefore, the aim of this study is to analyse the perceived functionality and benefits of a regional WHM network from companies’ perspective and to present initial results on this specific topic. Methods An explorative qualitative case study was conducted analysing ERZgesund, a WHM network in a rural region in Germany. Twenty-two companies that participated in the network were interviewed about their experiences and perceived advantages and disadvantages participating in the WHM network ERZgesund. Results The findings show that the network has raised awareness about WHM among the companies, provides opportunities for exchange of knowledge and experiences, and generates or strengthens collaboration. The positive effects were enhanced by the network’s structure, such as regionality and a direct contact person. Nevertheless, some companies stated that they would welcome a higher level of participation and transparency. Conclusion Overall, it becomes clear that a WHM network can be a valuable tool to emphasize the relevance of WHM to companies. Therefore, further studies should validate and intensify the research on WHM networks to ensure a long-term benefit from the network.